Potensi Limbah Pertanian dan Perkebunan sebagai Sumber Pakan Ternak Ruminansia Berdasarkan Daya Dukung Nutrisi (BK, PK, dan TDN) di Kabupaten Paser, Kalimantan Timur - Nurjannah, I; Fanani, A F (PETERPAN (Jurnal Peternakan Terapan), 2026)
Paser Regency in East Kalimantan Province has considerable potential in the agricultural and plantation sectors, which generate substantial amounts of biomass residues that can be utilized as alternative feed resources for ruminant livestock. However, quantitative evaluations of the contribution of these residues to regional feed availability remain limited. This study aimed to assess the potential of agricultural and plantation residues as sources of ruminant feed in Paser Regency based on the availability of dry matter (DM), crude protein (CP), and total digestible nutrients (TDN), as well as to estimate the regional feed carrying capacity. This research employed a descriptive quantitative approach using secondary data obtained from the official publication "Kabupaten Paser Dalam Angka 2025". Data on harvested areas and production of major agricultural and plantation commodities were used to estimate the potential biomass residues and their nutrient contents. Feed carrying capacity was calculated by comparing the total nutrient availability with the annual feed requirements per livestock unit (LU). The results showed that agricultural residues produced approximately 32,635.46 tons of DM, 24,070.64 tons of CP, and 14,464.24 tons of TDN. Based on these values, the feed carrying capacity was estimated at 14,307 LU based on DM, 99,891 LU based on CP, and 9,211 LU based on TDN, with TDN acting as the limiting factor. Compared with the total ruminant population of 16,768.88 LU in 2024, agricultural residues could supply about 54.9% of the feed requirement. Plantation residues generated larger amounts of biomass nutrients but contributed only about 316 LU due to limitations in nutrient balance and digestibility. Overall, agricultural and plantation residues have complementary roles as local feed resources. Their integrated utilization through appropriate feed formulation can enhance feed availability and support sustainable ruminant livestock development in Paser Regency.